2007
DOI: 10.1002/cncr.22922
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone‐related protein varies with sex and androgen status in nonsmall cell lung cancer

Abstract: BACKGROUND. In nonsmall cell lung cancer, tumor parathyroid hormone‐related protein (PTHrP) expression predicts longer survival in women but not in men. To explain the sex‐dependent survival effect, the authors proposed that hormonal influences decrease PTHrP in men versus women, that PTHrP inhibits tumor growth, and that the effect is greater in women than in men. The objectives of this study were to compare lung carcinoma PTHrP expression and carcinoma growth in male and female mice and to determine whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Although it has not been studied in lung, androgen and progesterone have been shown to exhibit overlapping gene regulatory action (Ghatge et al 2005). Lung cells have been shown to express receptors for and be responsive to both progesterone (Press & Greene 1988, Hagen et al 1990) and androgen (McDoniels-Silvers et al 2002, Card et al 2006, Montgrain et al 2007) and therefore, it may be that circulating androgen in the male substitutes for progesterone, enhancing the effect of the administered estrogen. On the other hand, circadian patterns of other hormones, such as growth hormone, differ between males and females (Chowen et al 2004) and these too may have effects on tumor progression.…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…Although it has not been studied in lung, androgen and progesterone have been shown to exhibit overlapping gene regulatory action (Ghatge et al 2005). Lung cells have been shown to express receptors for and be responsive to both progesterone (Press & Greene 1988, Hagen et al 1990) and androgen (McDoniels-Silvers et al 2002, Card et al 2006, Montgrain et al 2007) and therefore, it may be that circulating androgen in the male substitutes for progesterone, enhancing the effect of the administered estrogen. On the other hand, circadian patterns of other hormones, such as growth hormone, differ between males and females (Chowen et al 2004) and these too may have effects on tumor progression.…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…In addition to BMP-6, PTHrP has now been shown to function as an paracrine or autocrine growth factor to suppress the growth of transformed cells, such as human astrocytes and hepatoma cells (hep G2) (Li et al1996;Shankar et al 2000). Although based on the hypercalcemic effect of PTHrP, PTHrP is defined as a potential activation factor which endows tumor cells with a special property they require to establish and grow in bone, more and more clinical evidences have indicated that PTHrP expression in primary tumors connote prolonged survival in some types of human cancer such as breast cancer (Henderson et al 2006;Bakre et al 2002), hepatoma (Li et al 1996) and lung cancer (Montgrain et al 2007). Midregion PTHrP (38-94) restrains MDA-MB-231 growth and accelerates cell death through inducing the expression of Bcl-xs, Bad, Rip1 and caspases (Luparello et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…PTHrP 1-34 was measured in the samples of combined lysate and conditioned medium by our non-equilibrium competition radioimmunoassay, as described previously. 18,20 We calculated the average and standard deviation of the PTHrP level in wells exposed only to vehicle. To determine effects of a compound on cancer cell PTHrP expression, we expressed the difference in PTHrP vs. the control level as a multiple of the standard deviation, i.e., (PTHrP compound -PTHrP control )/SD control .…”
Section: Discussionmentioning
confidence: 99%
“…The lung cancer cells were plated in a high throughput format, treated with mixtures one at a time and then assayed for PTHrP. 18 If a mixture reduced the PTHrP level compared to vehicle treated cells, then one or more of the compounds in the mixture must inhibit PTHrP expression. The inhibitory compound or compounds has the chemical group at the specific diversity position that characterizes all the compounds in that particular mixture.…”
Section: Methodsmentioning
confidence: 99%